If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3y-6(9y-6)=3-4(9-y)
We move all terms to the left:
-3y-6(9y-6)-(3-4(9-y))=0
We add all the numbers together, and all the variables
-3y-6(9y-6)-(3-4(-1y+9))=0
We multiply parentheses
-3y-54y-(3-4(-1y+9))+36=0
We calculate terms in parentheses: -(3-4(-1y+9)), so:We add all the numbers together, and all the variables
3-4(-1y+9)
determiningTheFunctionDomain -4(-1y+9)+3
We multiply parentheses
4y-36+3
We add all the numbers together, and all the variables
4y-33
Back to the equation:
-(4y-33)
-57y-(4y-33)+36=0
We get rid of parentheses
-57y-4y+33+36=0
We add all the numbers together, and all the variables
-61y+69=0
We move all terms containing y to the left, all other terms to the right
-61y=-69
y=-69/-61
y=1+8/61
| 13x-3(3x-1)=3x-12 | | -3p-5(5-2p)=4(p-2)-5 | | 4y-3=2y=27 | | (2x^2)+5x-250=0 | | 9k+7=9-8 | | 9k+7K=9-8 | | 3y/2+y/6=35/3 | | (9-z)(5z-3)=0 | | 64-48÷6×4+8=x | | 3x+2/12-3x+4/24=3/8 | | 3x^=108 | | -7+3x=62 | | -7+3x=41 | | 3/10x-4/5=-2 | | n=123n+2 | | 3(x+1)=3(x+3)+x-3 | | 2/5=5x+15/2x+6 | | -4(2x+5)-2x=3(11-4x)+3x | | 7(2x)+3x=100 | | 4(2x-10)-5(x-3)=5-6x | | 2x-66=58 | | 6x+(-3x)=15-2x | | x/2+x/5=7/1 | | 6x-7x+1=0 | | 2x+3/5=5 | | g-12=-4 | | g-12=4 | | 5x2-98=3x2 | | (g-12)^2=16 | | 11x-18x=-72 | | -2.2+.3x=2.9 | | 20x+(x+24)=90 |